Família e escola : uma reflexão sobre a percepção da família em relação à escola - COSTA, Jociane de Lima (2020)
The research aimed to reflect about the perceptions of student's relatives concerning the school and their contributions in their children education. During the internship at the school, it was verified that the school is taking the relatives responsibilities resulting in negatives consequences to students learning. The study begun with the literature review about the concepts of families, once it is the first and maybe the most important reference institution to kids. During the data collect, it was realized semi structured interview with the student's families, their socio-economic profiles were characterised and their answers were analyzed. It was verified that the families see the school as a place for learning, within which their children can have a promising future and “have a degree”. That is the importance to the children formation, if they reach the school’s final goals. The families also reported that the school needs better structure, better lunch, better teachers, including learning reinforcement that should be provided by the school, however the families do not include themselves in the process.